2010
DOI: 10.1111/j.1524-4741.2010.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Using National Quality Forum Breast Cancer Indicators to Measure Quality of Care for Patients in an AVON Comprehensive Breast Center

Abstract: In April 2007, the National Quality Forum (NQF) endorsed the first nationally recognized hospital-based performance measures for quality of care for breast cancer. The aim of this study was to measure quality of care at our AVON Center for Breast Care (AVONCBC) using these indicators. We retrospectively reviewed tumor registry and medical records of females under age 70 diagnosed with breast cancer in years 2005-2006. For patients diagnosed with hormone receptor negative breast cancer, 22 of 29 (75.9%) and 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…It is noteworthy that most women in our study were found to have received HT, albeit many outside the recommended time frame. Whereas reasons for never compliance were largely nonmodifiable (such as patients moving out of the country) and consistent with other studies, 19,20 the reasons for delays in care, though multifactorial, are potentially modifiable through innovations in care delivery. Despite a largely immigrant population, we found no difference in insurance status between compliant and noncompliant patients.…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that most women in our study were found to have received HT, albeit many outside the recommended time frame. Whereas reasons for never compliance were largely nonmodifiable (such as patients moving out of the country) and consistent with other studies, 19,20 the reasons for delays in care, though multifactorial, are potentially modifiable through innovations in care delivery. Despite a largely immigrant population, we found no difference in insurance status between compliant and noncompliant patients.…”
Section: Discussionsupporting
confidence: 82%
“…A C C E P T E D ACCEPTED MANUSCRIPT 8 The second QI which scored worse after certification was patients with invasive breast cancer receiving just 1 operation (83.1% vs 80.4 %, p>0.001). This is likely due to the attempt of the new accredited units to maximize the proportion of patients treated with breast conserving surgery, leading to more secondary additional resections or mastectomies in order to obtain clear margins.…”
Section: A N U S C R I P Tmentioning
confidence: 98%
“…, A Costa (7), M Danei (9), A Denk (10), G Emons (11), K Friedrichs (12), N Harbeck (13), M Kiechle (14), U Koheler (15), S Kuemmel (16), N. Maass (8), C. Marth (17), A Prové (18), R. Kimmig (19), C Rageth (20), L Regolo (21), L Salehi (22), D Sarlos (23), C Singer (24), C Sohn (4), G Staelens (25), C Tinterri (26) …”
mentioning
confidence: 99%
“…También nos parece importante definir a nivel de la Sociedad de Mastología, estándares mínimos y óptimos que permitan inicialmente que cada centro se autoevalúe para en un futuro plantear la necesidad de acreditación [8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionunclassified